Conventional and microwave sintering of CaCu(3)Ti(4)O(12)/CaTiO(3) ceramic composites: non-ohmic and dielectric properties - Ramirez, M. A. [UNESP]; Bueno, Paulo Roberto [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Iop Publishing Ltd, 2008)
The non-ohmic and dielectric properties as well as the dependence on the microstructural features of CaCu(3)Ti(4)O(12)/CaTiO(3) ceramic composites obtained by conventional and microwave sintering were investigated. It was demonstrated that the non-ohmic and dielectric properties depend strongly on the sintering conditions. It was found that the non-linear coefficient reaches values of 65 for microwave-sintered samples and 42 for samples sintered in a conventional furnace when a current density interval of 1-10 mA cm(-2) is considered. The non-linear coefficient value of 65 is equivalent to 1500 for samples sintered in the microwave if a current interval of 5-30 mA is considered as is shortly discussed by Chung et al (2004 Nature Mater. 3 774). Due to a high non-linear coefficient and a low leakage current (90 mu A) under both processing conditions, these samples are promising for varistor applications. The conventionally sintered samples exhibit a higher relative dielectric constant at 1 kHz (2960) compared with the samples sintered in the microwave furnace (2100). At high frequencies, the dielectric constant is also larger in the samples sintered in the conventional furnace. Depending on the application, one or another synthesis methodology is recommended, that is, for varistor applications sintered in a microwave furnace and for dielectric application sintered in a conventional furnace.